PELATIHAN AYAT JURNAL PENYESUAIAN PADA PERUSAHAAN DAGANG BAGI SISWA/I SMA - Michelle Aveline; Agustin Ekadjaja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) teaching assistance program delivered material on adjusting journal entries for trading companies at SMA Budi Mulia Jakarta. Accounting is often perceived as a difficult and complex subject for students, making it difficult for them to grasp the fundamental concepts of accounting, let alone adjusting journal entries. Through this program, it is expected that students will be able to understand and master the preparation of adjusting journal entries, while university students can enhance both their hard skills and soft skills, which will later be beneficial in the workplace. The teaching assistance at SMA Budi Mulia Jakarta began on August 4, 2025, covering the definition and examples of adjusting journal entries related to deferrals and accruals. The material on adjusting journal entries was delivered from August 4 to September 1, 2025. The learning process was carried out interactively so that students could actively participate and increase their enthusiasm in the teaching and learning activities. This approach was intended to help students pay closer attention and engage in practicing the preparation of adjusting journal entries. The learning outcomes could be observed from the scores obtained in the daily assessments. The results showed that although students had not yet fully mastered the material on adjusting journal entries, there was a significant improvement compared to the previous daily assessments. Several students even managed to achieve perfect scores, indicating an increased understanding of adjusting journal entries. Program Merdeka Belajar Kampus Merdeka (MBKM) asistensi mengajar ini menyampaikan materi ayat jurnal penyesuaian bagi perusahaan dagang di SMA Budi Mulia Jakarta. Akuntansi dipandang sebagai mata pelajaran yang sulit dan rumit bagi siswa/i, sehingga mereka kurang mampu memahami konsep dasar akuntansi, apalagi jurnal penyesuaian. Dengan dilakukannya program ini, diharapkan para murid mampu memahami dan menguasai penyusunan ayat jurnal penyesuaian dan mahasiswa mampu meningkatkan hard skill sekaligus soft skill yang nantinya akan berguna di dunia kerja. Asistensi mengajar di SMA Budi Mulia Jakarta dimulai pada tanggal 4 Agustus 2025 yang membahas pengertian dan contoh ayat jurnal penyesuaian deferrals dan accruals. Materi ayat jurnal penyesuaian diberikan sejak tanggal 4 Agustus hingga 1 September 2025. Proses pembelajaran dilakukan secara interaktif agar para siswa/i dapat secara aktif berpartisipasi dan meningkatkan antusiasme mereka dalam kegiatan belajar mengajar. Pendekatan ini dilakukan agar siswa/i lebih fokus memperhatikan dan ikut serta mencoba menyusun jurnal penyesuaian. Hasil pembelajaran dapat dilihat dari nilai yang mereka peroleh ketika penilaian harian. Hasil penilaian harian menunjukkan bahwa siswa/i masih belum sepenuhnya memahami materi ayat jurnal penyesuaian, tetapi terdapat peningkatan signifikan dibandingkan penilaian harian sebelumnya. Terdapat beberapa siswa/i yang berhasil memperoleh nilai sempurna, hal ini mengindikasikan adanya peningkatan pemahaman mengenai ayat jurnal penyesuaian.